2015
DOI: 10.1107/s2053230x15000783
|View full text |Cite
|
Sign up to set email alerts
|

Structure of the dodecamer of the aminopeptidase APDkam598 from the archaeonDesulfurococcus kamchatkensis

Abstract: The crystal structure of the aminopeptidase APDkam589 from the thermophilic crenarchaeon Desulfurococcus kamchatkensis was determined at a resolution of 3.0 Å . In the crystal, the monomer of APDkam589 and its symmetry-related monomers are densely packed to form a 12-subunit complex. Single-particle electron-microscopy analysis confirms that APDkam589 is present as a compact dodecamer in solution. The APDkam589 molecule is built similarly to the molecules of the PhTET peptidases, which have the highest sequenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 31 publications
1
12
0
Order By: Relevance
“…The M18 family is widely distributed in all domains of life (14) while the M42 family is unique to prokaryotes (23). Several structures of archaeal M42 aminopeptidases have been studied (13,15,17,18,(24)(25)(26) but only one structure has been reported for bacteria (27). Franzetti et al (2002) described the first TET-aminopeptidase structure of the Haloarcula marismortui M42 aminopeptidase, consisting of twelve subunits adopting a tetrahedron-shaped quaternary structure (25).…”
Section: Introductionmentioning
confidence: 99%
“…The M18 family is widely distributed in all domains of life (14) while the M42 family is unique to prokaryotes (23). Several structures of archaeal M42 aminopeptidases have been studied (13,15,17,18,(24)(25)(26) but only one structure has been reported for bacteria (27). Franzetti et al (2002) described the first TET-aminopeptidase structure of the Haloarcula marismortui M42 aminopeptidase, consisting of twelve subunits adopting a tetrahedron-shaped quaternary structure (25).…”
Section: Introductionmentioning
confidence: 99%
“…In general, Trp residues do not often occur on the protein surface (Samanta et al 2000). Among 13,672 sequences from the IMG Database (Markowitz et al 2014) that have more than 30 % identity with the APDkam589 sequence, only 15 sequences contain six Trp residues, the same as in APDkam589 (Petrova et al 2015). All Trp residues of APDkam589 are located on the surface of the monomer and the dimer; and all Trp residues, except one (Trp49), are on the external surface of the APDkam589 molecule (Fig.…”
Section: Resultsmentioning
confidence: 97%
“…In the crystal, the symmetryrelated monomers of APDkam589 form a compact, tetrahedrally shaped, 12-subunit structure. Independently, single-particle electron microscopy analysis revealed that the APDkam589 molecule exists as a tetrahedral dodecamer in solution (Petrova et al 2015).…”
Section: Structure Of the Apdkam589 Moleculementioning
confidence: 99%
See 2 more Smart Citations